Digitalization of the Environmental Protection .......... 229 - Volkova, Yuliia; Leheza, Yuliia (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
This article is devoted to the problems of digitalization and regulatory and legal security of public information services in the field of environmental protection. The article focuses on establishing the essence and content of the security of public information services in the field of environmental protection, carries out a retrospective analysis of such a concept and establishes the current state of normative regulation of their use. The authors put forward the thesis that the regulatory framework ensuring the security of public information services in the field of environmental protection is an extensive set of legislative and subordinate legal acts, the current state of which requires systematization in order to achieve an adequate level of efficiency in exercising the right to information. The article emphasizes that the digital transformation of society in modern conditions is an objective process but is not always carried out in accordance with certain rules determined by national legislation, considering international legal principles and approaches to the consolidation and implementation of human rights and freedoms. Today, the issues of transformation of the social policy in the context of the development of the digital economy are relevant. High-quality and effective social protection in the conditions of informatization should be one of the main priorities of the state.